Association between long non coding RNA levels and hypertension mediated organ damage. (25th November 2020) - Marketou, M; Kontaraki, J; Patrianakos, A; Maragkoudakis, S; Plevritaki, A; Lempidakis, D; Theodosaki, O; Plataki, M; Papadaki, S; Vardas, P; Parthenakis, F
Abstract: Purpose: Long non coding RNAs (lncRNAs) are emerging as important components of regulatory networks underlying cardiovascular development and pathophysiology. They exhibit distinctive roles in modulating tissue-specific epigenomic states that are critical for the transcriptional and epigenetic reprogramming that may underpin cardiovascular disease pathogenesis. We investigated the association between gene expression levels of the lncRNAs CARMEN and FENDRR in peripheral blood mononuclear cells (PBMCs) and asymptomatic hypertension mediated organ damage. Methods: We included 56 patients with essential hypertension (38 women, mean age 77±8 years). Twenty nine normotensive individuals (14 women, mean age 76±10 years) were also included as controls. PBMCs were isolated and lncRNAs' expression levels were determined by quantitative real-time reverse transcription polymerase chain reaction. Hypertension mediated organ damage (MOD), namely carotid wall thickening, left ventricular hypertrophy, and albuminuria were assessed in all patients. Results: Hypertensive patients showed significantly higher CARMEN (19.95±5.9 versus 5.69±2.82, p<0.001) and FENDRR (37.7±11.8 versus 10.21±8.02, p<0.001) expression levels compared with controls. Increased CARMEN expression levels in PBMCs showed a significant relationship with the number of organs involved (r=0.49, p=0.001). No significant relationship was revealed for FENDRR levels. Conclusions: Our data reveal that in essential hypertension, increased CARMEN expression levels in PBMCs could be a marker of subclinical MOD. Further studies are needed to assess their role as potential biomarkers or future therapeutic targets in those patients. Funding Acknowledgement: Type of funding source: None